Problematics of hand arrest operation by KPK in the due process of perspective law - Parnitongan Malau (The International Journal of Politics and Sociology Research, 2023)
There has been a legal emergency in Indonesia's law enforcement, notably in terms of corruption, ever since the reformation. The purposes of this research are twofold: (1) to ascertain whether or not the hand arrest operation conducted by Komisi Pemberantasan Korupsi Indonesia (KPK) investigators is in accordance with Indonesian criminal procedure legislation, and (2) to ascertain whether or not the operation represents the rule of law in Indonesia. Specifically, this is an example of normative legal research. This thesis was written using a legal approach. The research found that KPK investigators' arrest operations are treated the same as any other arrest governed by Indonesia's Criminal Process Code, which requires many stages prior to being carried out (including eavesdropping and undercover operations). The purpose of this study is to analyze the existence of Hand Arrest Operation by Komisi Pemberantasan Korupsi Indonesia (KPK) investigators in Indonesian criminal procedural law, as well as to examine whether hand arrest operation by KPK investigators reflects Indonesian criminal procedure law which adheres to due process of law. The type of research in this research is normative legal research. While the approach taken in writing this thesis is statutory. The results of the study show that the existence of the arrest operation by KPK investigators in the Indonesian criminal procedure law can be concluded to be the same as the ordinary arrest regulated in the Criminal Procedure Code, which must be preceded by a series of actions such as as wiretapping and undercover operations before the arrest operation is carried out.